Weaknesses in motivation and in establishing a meritocratic system: A portrait of the Portuguese public administration - Adriana Z. F. C. Nishimura; Ana Moreira; Maria José Sousa; Manuel Au-Yong-Oliveira (Administrative Sciences, 2021)
The complexities of Public Administration have gained the growing attention of scholars around the world, mainly due to the impacts of the reforms implemented under the doctrine of New Public Management (which aims to apply concepts and practices of private management in public management) on civil servants. The aim of this study is to find out how Portuguese citizens evaluate the Portuguese Public Administration under the aspects of bureaucracy, organisation of human resources, innovation, skills and attitudes of civil servants, its motivation and recognition; and to verify if there are differences of opinion between respondents working in public sector and respondents from other sectors. This study follows a quali-quantitative approach, and data were collected through an online survey in the period from June to December 2020. The survey was answered by 1119 citizens from all districts of Portugal. The main findings reveal a still high level of bureaucracy in the Portuguese Public Administration; weaknesses in the management of human resources, namely regarding the motivation and recognition of civil servants; and difficulties in the establishment of a meritocratic system of recruitment and performance evaluation of civil servants. Statistically significant evaluation differences (chi-square test and non-parametric Mann-Whitney U tests, involving five hypotheses) were found between the public sector and other sectors, except for the motivation variable.
Keywords: 350; bureaucracy; civil servants; meritocracy; motivation; new public management; Portugal; Portuguese public administration; public administration